Consumer demand heterogeneity and valuation of value-added pulse products: a case of precooked beans in Uganda - Aseete, Paul; Katungi, Enid M.; Bonabana-Wabbi, Jackline; Birachi, Eliud Abucheli; Ugen, Michael Adrogu (Springer, 2018)
Background